Theoretical model for heat transfer in the single crystal making - Chejne, Farid; Flórez, Whady; Ragimova, Tamila; Hernández, Juan (Revista Facultad de Ingeniería Universidad de Antioquia, 2002)
A mathematical model has been developed that describes the heat transfer process during melt solidification and to define axial and radial thermal profile in both phases, solid and liquid. With this model we can obtain the geometric interface profile. Also we can study the influence of the main parameters such as the Biot number, the Peclet number and the lowering rate of the ampoule. We have used this model to give a conceptual explanation about heat transfer phenomena involved in another process like single crystal making.